Predictors of Primary Care Physician Practice Location in Underserved Urban or Rural Areas in the United States: A Systematic Literature Review. (September 2016) - Goodfellow, Amelia; Ulloa, Jesus G.; Dowling, Patrick T.; Talamantes, Efrain; Chheda, Somil; Bone, Curtis; Moreno, Gerardo
Abstract : Purpose: The authors conducted a systematic review of the medical literature to determine the factors most strongly associated with localizing primary care physicians (PCPs) in underserved urban or rural areas of the United States. Method: In November 2015, the authors searched databases (MEDLINE, ERIC, SCOPUS) and Google Scholar to identify published peer-reviewed studies that focused on PCPs and reported practice location outcomes that included U.S. underserved urban or rural areas. Studies focusing on practice intentions, nonphysicians, patient panel composition, or retention/turnover were excluded. They screened 4, 130 titles and reviewed 284 full-text articles. Results: Seventy-two observational or case–control studies met inclusion criteria. These were categorized into four broad themes aligned with prior literature: 19 studies focused on physician characteristics, 13 on financial factors, 20 on medical school curricula/programs, and 20 on graduate medical education (GME) programs. Studies found significant relationships between physician race/ethnicity and language and practice in underserved areas. Multiple studies demonstrated significant associations between financial factors (e.g., debt or incentives) and underserved or rural practice, independent of preexisting trainee characteristics. There was also evidence that medical school and GME programs were effective in training PCPs who locate in underserved areas. Conclusions: Both financial incentives and special training programs could be used to support trainees with the personal characteristics associated with practicing in underserved or rural areas. Expanding and replicating medical school curricula and programs proven to produce clinicians who practice in underserved urban or rural areas should be a strategic investment for medical education and future research. Abstract : Supplemental Digital Content is available in the text.